Reverse Time During Current Relay Performance to Support the Protection System Practicum - Wahyono, Wahyono; sumarno, F. Gatot; W, wiwik Purwati; margana, margana; suwarti, Suwarti; N., Ajie Pribadi (Politeknik Negeri Semarang, 2022)
””Overcurrent Relay is one of the protection system tools in the electricity network. Overcurrent Relay works based on the increase in fault current that exceeds a certain safety value and a certain period of time. The type of relay that will be used in this test is the IDMT NX203A Overcurrent Relay. The purpose of this test is to get a good practicum module and to prove the inverted time relay characteristic curve according to British Standard BS142. In the test, the tool to be assembled is tested for its work function so that in data collection errors can be avoided while the relay on the module will be given a current setting of 2A; 3A; and 4A with TMS0.05; 0.5; and 1.0 which will be connected to a digital timer so that if the fault current exceeds the setting current, the relay will automatically give a signal and the digital timer will show the time when the current is cut off. The final result is a practicum module where each tool functions under normal working conditions and a graph of time against relay current for setting current 2A, fastest time 0.498s at 9A fault current and 0.05 TMS, longest time 12.991s at 4A TM fault current. . 1.0. Current setting of 3A for the fastest time is 0.572s at fault current of 9A and TM 0.05, for the longest time is 35.854s at fault current of 4A and TM 1.0. Current setting of 4A for the fastest time is 0.708s at fault current of 9A and TM 0.05, for the longest time is 55.979s at fault current of 5A and TM 1.0.